PENGARUH PERIKLANAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE PADA SITUS BELANJA ONLINE (Studi Kasus pada Pengguna E-commerce Elevenia Di Kota Semarang) - Shri Isyanahapsari; Sendhang Nurseto (Universitas Diponegoro, 2018)
In Indonesia there are many online marketplace that is place where sellers can create an account and peddling wares. Research results on the website Elevenia shows that a positive and influential advertising significantly to purchasing decision. The influence of advertising and the quality of service to the most influential buying decision is positive and significant. The conclusions of the study of advertising and the quality of service a positive effect against purchasing decisions.